The Impacts of the South China Sea Disputes between Vietnam and China on the Vietnamese Government’s Perspectives on Joining the Belt Road Initiative - Dao, Ngoc (My University, 2021)
The international nexus of security and economic cooperation is a complicated issue especially between countries that are in asymmetric positions like Vietnam and the People Republic of China (China). Living next to a giant neighbor has been creating Vietnam both challenges and opportunities in the past two thousand years since the first independent state form of Vietnam was established. The challenge for Vietnam is how to successfully perform its political maneuvering to get the most benefits from economic cooperation and at the same time not to damper its ideological independence and sovereignty. This thesis looks into two aspects acting as two separated, but also mutual- affected case studies, the South China Sea disputes (security) and the Belt Road Initiative (BRI) (economic cooperation). By qualitative analysis, I wanted to give a thought on how a small and weak country (Vietnam) can manage in the challenging situation when putting the economic benefits and the territorial rights (from Vietnam’s point of view) on the same scale. The thesis concludes that Vietnam has faced a greater challenge in joining the BRI and the actual implementation of the BRI in Vietnam has been still very slow. The Vietnamese government is willing to support the BRI as long as they can get benefits from the BRI, while not dampening its political motivation and persistence with their agenda on the South China Sea. Vietnam is therefore hedging its position towards the PRC.
Keywords: The South China Sea, Belt Road Initiative, Security, Economic Cooperation